Difficult literature on Goodreads: reading Alexis Wright's The Swan Book. Issue 1 (2nd January 2022) - Stinson, Emmett; Driscoll, Beth
ABSTRACT: This article considers Alexis Wright's novel The Swan Book (2013) and argues that the text's difficulty, which recalls literary modernism, should be understood as a Latourian affordance. An affordance is a quality that facilitates interaction between objective and subjective elements within readerly networks. To analyze this affordance, we examine two influential accounts of literary difficulty: George Steiner's (1978) conceptual schema of four kinds of difficulty (contingent, modal, tactical and ontological) and Leonard Diepeveen's (2003) historicised account of modernist difficulty and the various rhetorical claims made about its value. We counterpoise these accounts with an analysis of 99 Goodreads reviews of The Swan Book. We find that many Goodreads reviews foreground affective and social qualities, in which difficulty becomes a shared problem for readers. They thereby resist the traditional imperative to aesthetic judgment and offer a new set of aesthetic responses to difficulty, which we term post-critical reviews.